2022
DOI: 10.3390/rs14020366
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Evolution of the Carbon Fluxes from Bamboo Forests and their Response to Climate Change Based on a BEPS Model in China

Abstract: Carbon flux is the main basis for judging the carbon source/sink of forest ecosystems. Bamboo forests have gained much attention because of their high carbon sequestration capacity. In this study, we used a boreal ecosystem productivity simulator (BEPS) model to simulate the gross primary productivity (GPP) and net primary productivity (NPP) of bamboo forests in China during 2001–2018, and then explored the spatiotemporal evolution of the carbon fluxes and their response to climatic factors. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…Methodologically, different techniques have been used to estimate vegetation WUE and to unravel its drivers over multiple spatiotemporal scales. The flux tower can offer reliable carbon-water flux observations for estimating WUE in forest ecosystems, while field measurements of WUE by flux towers are scarce in the Chinese subtropical forest region [35]. Moreover, the footprint of a flux tower is limited from a few kilometers in the best case, which limits our understanding of forest WUE and its driving factors over large spatial scales [35].…”
Section: Introductionmentioning
confidence: 99%
“…Methodologically, different techniques have been used to estimate vegetation WUE and to unravel its drivers over multiple spatiotemporal scales. The flux tower can offer reliable carbon-water flux observations for estimating WUE in forest ecosystems, while field measurements of WUE by flux towers are scarce in the Chinese subtropical forest region [35]. Moreover, the footprint of a flux tower is limited from a few kilometers in the best case, which limits our understanding of forest WUE and its driving factors over large spatial scales [35].…”
Section: Introductionmentioning
confidence: 99%
“…Bamboo forests possess great potential for carbon sequestration, and they are the most likely type of forest to enter the emission reduction market [32]. Several studies have reported the role of bamboo forests in global carbon cycling [19,33] as well as their successful use in absorbing wastewater from agriculture, industry, animal husbandry, and pollution. Bamboo is particularly useful in terms of air protection as a good material for carbon sequestration.…”
Section: Bamboo For Environmental Protectionmentioning
confidence: 99%
“…It sequesters variable carbon concentrations from the surroundings and maintains carbon concentration points through the carbon cycle (Abebe et al 2021). Bamboo conducts the carbon cycle metabolism for stabilizing carbon concentrations and the soil environment through the carbon cycle and biomass (Kang et al 2022). Bamboo maintains the industrial economic value and natural resources from disaster.…”
Section: Ecological Value Of Major Bamboo Speciesmentioning
confidence: 99%
“…Bamboo governs an imperative role in the maintenance of climatic factors (Kang et al 2022). Bamboo sequesters variable carbon and has a different growing period (Bradshaw 2012).…”
Section: Introductionmentioning
confidence: 99%